Analisis Faktor Penentu Minat Nelayan terhadap Budidaya Rumput Laut Menggunakan Regresi Linear (Studi Empiris di Kabupaten Sumenep Jawa Timur) - Aini Mazaya Najihan; Slamet Widodo; Amanatuz Zuhriyah; Jeter Donald Siwalette (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Mariculture is growing rapidly in response to declining capture fisheries and increasing global demand for seafood. In coastal areas like Saronggi Subdistrict, Sumenep Regency, fishermen often experience seasonal limitations in capture fisheries, which affect their income stability. As a result, many begin to consider seaweed farming as an alternative livelihood. This study aims to examine the level of fishermen's interest in seaweed farming and identify the factors that influence it. The research was conducted from August to December 2024 in Saronggi Subdistrict, Sumenep Regency, East Java Province. A total of 30 respondents were selected purposively, focusing on fishermen who were either currently engaged in or considering seaweed farming. The study employed a quantitative descriptive approach using primary data collected through structured interviews. Data analysis was carried out using multiple linear regression to determine the relationship between selected variables and fishermen’s interest in seaweed farming. Preliminary findings indicate a generally high level of interest among fishermen in seaweed farming. Several socio-economic and institutional factors, such as age, fishing experience, and access to markets, appear to be associated with this interest, suggesting potential leverage points for policy or community-based intervention. Further analysis will explore how these variables interact and what this implies for supporting livelihood transitions in coastal communities.